Estrategia de marketing para incrementar las ventas en la empresa aromatizantes Aroma’x, Iquitos, 2022 - Orbe Castillo, Gregory (2023)
The main objective of this study is to know how the marketing mix strategies of the company Aromatizantes Aroma'X, Iquitos 2022 are related to their sales. This research is descriptive correlational with a quantitative approach because characteristics of the medium that is the object of study are described. Each variable will be described in this research project without changing its actual state. According to the reliability coefficient scale, the cases processed and the Alpha reliability coefficient for variable 1: Marketing mix strategies have a high level of confidence. The reliability coefficient of Cronbach's Alpha is equal to 0.670. Cronbach's alpha is equal to 0.765, based on the scale for variable 2: Sales of processed boxes, obtaining the same level of confidence. The sigma (two-sided) value is equal to 0.000 and the Pearson correlation value is equal to 0.752, indicating a significant positive correlation. determining that the marketing mix strategies and the sales of Aroma'x flavorings have a significant relationship.